A Multi-state Model of Functional Disability and Health Status in the Presence of Systematic Trend and Uncertainty. Issue 1 (2nd January 2021) - Sherris, Michael; Wei, Pengyu
Abstract : This article proposes a multi-state model of both functional disability and health status in the presence of systematic trend and uncertainty. We classify each individual observation along two dimensions health status (other than disability) and disability—and use the multi-state latent factor intensity model to estimate the transition rates. The model is then used to calculate (healthy) life expectancy and price a variety of insurance products. We illustrate the importance of various factors and quantify the potential losses from model misspecification. Our results suggest that insurers should pay great attention to health status, trend, and systematic uncertainty in disability/mortality modeling and insurance pricing. We also find that integrating long-term care (LTC) insurance with a life annuity can help to reduce systematic uncertainties.